Design of Information Systems: A Software Engineering Approach - Singh, Gurpreet (My University, 2007)
In most of the organizations in India, information system are developed using an unstructured approach, which leads to faulty and ineffective systems. Many systems fail due to the reason that they are not developed using any proper methodology. Moreover information system development is expensive and is often unreliable. The goal of software engineering is to face this software crisis. Software Engineering is a discipline that aims at providing methodologies or engineering approaches for development of information system. It is a combination of two things, software and engineering, by combining these two things Software Engineering can be defined as the systematic approach to the development, operation & maintenance of software. Analysis of various studies reveals that the researches mainly concerns with reliability and testing of software using different techniques and are silent about the techniques used for overall development of information system. Hence a survey of relevant studies establishes a need for applying the software engineering approach for information system development. In this study emphasis is given on applying software engineering approach for overall development of information system. Various aspects of software engineering like complexity, correctness, maintability and reusability have been introduced and information system of University has been designed by applying various software engineering approaches. An analysis of different system development process models that are used to guide the analysis, design, development and maintenance of information system have been undertaken in this work, and a new model for the development of system has been proposed. On the basis of the above study it has been recommended that the software engineering approach should be applied while developing information system for the University.
Keywords: Information systems; Software engineering; Computer science